Ex Situ Conservation of Rafflesia patma BLUME (Rafflesiaceae) - Sofi Mursidawati; Ngatari Ngatari; Irawati Irawati; Sarah Cardinal; Richa Kusumawati (Sibbaldia, 2015)
Plants in the genus Rafflesia (Rafflesiaceae) bear the largest flowers in the world. Almost all members of this holoparasitic plant family have limited ranges and are rare or threatened. This genus is therefore important from a scientific and conservation perspective. An ex situ conservation collection of a population of Rafflesia patma Blume has been monitored at Bogor Botanic Garden (BBG) since 2004, the first time that this has ever been done. Studies have been made, including propagation trials on both seed and vegetative material at BBG. Of all the propagation methods tested, grafting on to the host plant Tetrastigma scariosum (Blume) Planch proved to be the most successful for growing R. patma, resulting in blooming having occurred seven times since 2010. Grafting is the quickest way to propagate Rafflesia in cultivation. This cultivation process provides a new hope for the conservation of this endangered and charismatic genus. This paper describes the methods trialled including both unsuccessful techniques as well as those which resulted in blooming events.